Enhancement of cyanobacterial control by fungi degraded palm oil trunk - Yusof, Tengku Nadiah; Lari, Mohd Rafatullah; Ismail, Norli; Zainuddin, Zarina; Lalung, Japareng (Malaysian Society for Microbiology, 2018)
The elliptic azimuthal anisotropy coefficient (v2) is measured for charm (D0) and strange (K0 S, Λ, Ξ−, and Ω−) hadrons, using a data sample of p þ Pb collisions collected by the CMS experiment, at a nucleonnucleon center-of-mass energy of ffiffiffiffiffiffiffi sNN p ¼ 8.16 TeV. A significant positive v2 signal from long-range azimuthal correlations is observed for all particle species in high-multiplicity p þ Pb collisions. The measurement represents the first observation of possible long-range collectivity for open heavy flavor hadrons in small systems. The results suggest that charm quarks have a smaller v2 than the lighter quarks, probably reflecting a weaker collective behavior. This effect is not seen in the larger PbPb collision system at ffiffiffiffiffiffiffi sNN p ¼ 5.02 TeV, also presented.